Application of Lavender Aromatherapy to Mrs. M with Endometriosis Cysts Post Htsob Operation in Reducing Pain in the Treatment Room on the 2nd Floor of the Iman Sudjudi Pavilion, Gatot Soebroto Hospital - Kamilah, Lilis (Akademi Keperawatan RSPAD Gatot Soebroto, 2021)
Endometriosis cysts or chocolate cysts are lesions located in the ovaries. Endometriosis cysts as much as 5-10% can be found in women of reproductive age. Endometriosis cysts not only cause pain during menstruation or outside the menstrual cycle, but this condition can interfere with ovulation, interfere with the condition of the internal reproductive organs so that the interaction of egg cells and sperm is disrupted and interfere with implantation. The purpose of this case study is to describe nursing care with the provision of lavender aromatherapy to reduce the intensity of the pain scale. The method used is a descriptive method using a case study approach method and the research data are presented in the form of giving lavender aromatherapy to patients with endometriosis cysts after Bilateral Hysterectomy Salphingo Ooverectomy surgery. The results of this case study showed that patients with endometriosis cysts after Bilateral Hysterectomy Salphingo Ooverectomy surgery found that giving lavender aromatherapy could affect the decrease in the intensity of the pain scale. The conclusion of this case study can be concluded that the implementation of aromatherapy has succeeded in reducing the intensity of the pain scale